KONSEP SENTRALISASI SISTEM PENGELOLAAN ZAKAT DALAM PEMBERDAYAAN EKONOMI UMAT - Yuni Sudarwati; Nidya Waras Sayekti (Jurnal Ekonomi & Kebijakan Publik, 2011)
The Amendment to The Law Number 38 of 1999 on Management of Zakatbeing discussed by Parliament today. The discussion looks contestationbetween civil society and the state, which there is the tendency ofgovernments who want to take the role of the management of alms fromthe public and civil society that sustain the management of zakat in ordernot to be taken by the government. This paper is intended to identify acentralized system that will be applied in a change of Act No. 38 of 1999concerning the management of zakat. The conclusion that can be given tothe implementation of centralized management system of zakat, infaq, andshodaqoh is centralization allows coordination both in fundraising andspreading. So expect more maximum utilization. But there must be clearseparation of roles between, the government and the private sector in themanagement of zakat, infaq, and shodaqoh. The government acts asregulator and supervisor. While zakat management institutionsstrengthened its position by being given a wider latitude for economicimprovement and community welfare.